Economic analysis and public enterprises - Turvey, Ralph (Totowa, N.J. : Rowman and Littlefield, 1972)
This book falls into two parts. In the first seven chapters the author sets out principles of optimal pricing and investment which were found useful in P.I.B. public enterprise studies. The remainder are reprints from P.I.B. reports on urban transport, island shipping, gas and coal. The first five chapters are about financial performance, second-best, the choice between one or more prices when marginal cost differs between consumers, and how to decide whether it is worth improving quality.
Includes bibliographical references.
lje 13/12/18
Loans
Keywords: Government business enterprises; Government business enterprises